This accident of being lost - Goos, Melaina (My University, 2019)
The three posters together symbolize reflection and the healing process. The images used for them were photographed in Elk Island, outside of Edmonton, using a lens that divides and distorts the image. The photographed images are blurry, and broken into separate parts and are a reflection of being lost and disoriented. The photographs have muted/minimal colour and progressively get lighter throughout the three posters. It represents the stages of healing and supports the quotes used for each of the posters. The posters have nature as the subject as it is crucial for Indigenous peoples to be connected to the land to heal from the trauma experienced from colonization.
Keywords: typography; poster design; This Accident of Being Lost; Leanne Betasamosake Simpson